Male EFL Teachers’ Perspectives on Error Correction in Language Education: - Hamzehloo, Maryam; Sorayyaei Azar, Ali; Hamzehloo, Mahdi (LANGUAGE ART, 2025)
Error analysis research has highlighted language learners’ varied preferences regarding oral error correction in classroom settings. However, limited attention has been given to investigating gender differences in EFL teachers’ attitudes towards error correction. This study explores male EFL teachers’ perspectives on error correction in both male and female classes, encompassing aspects such as necessity, frequency, timing, type, method, and delivery agent. Participants included 60 male teachers with varying levels of experience in teaching English in Iran. Utilizing a questionnaire developed by Fukuda (2006), a paired sample t-test is used to compare attitudes between male teachers in segregated male and female classes. While no significant differences were found in the perceived necessity and frequency of error correction, variations emerged in timing, type, method, and delivery agent preferences. The findings offer valuable insights for teacher educators, policymakers, and English language instructors, aiding in the enhancement of error correction strategies in EFL classrooms.